User Testing with Microinteractions: Enhancing a Next-Generation Repository - Gonzales, Sara; Carson, Matthew B.; Viger, Guillaume; O'Keefe, Lisa; Allen, Norrina B.; Ferrie, Joseph P.; Holmes, Kristi (Information Technology and Libraries, 2021)
Enabling and supporting discoverability of research outputs and datasets are key functions of university and academic health center institutional repositories. Yet adoption rates among potential repository users are hampered by a number of factors, prominent among which are difficulties with basic usability. In their efforts to implement a local instance of InvenioRDM, a turnkey next generation repository, team members at Northwestern University’s Galter Health Sciences Library & Learning Center supplemented agile development principles and methods and a user experience design-centered approach with observations of users’ microinteractions (interactions with each part of the software’s interface that requires human intervention). Microinteractions were observed through user testing sessions conducted in Fall 2019. The result has been a more user-informed development effort incorporating the experiences and viewpoints of a multidisciplinary team of researchers spanning multiple departments of a highly ranked research university.